Variable neighborhood search : 7th International Conference, ICVNS 2019, Rabat, Morocco, October 3-5, 2019, Revised selected papers /: 7th International Conference, ICVNS 2019, Rabat, Morocco, October 3-5, 2019, Revised selected papers. (2020) - Unknown
No abstract available